COASTAL MOSLEM’S CREATIVE ECONOMY DEVELOPMENT MODEL : CASE STUDY IN KENJERAN SURABAYA - Tika Widiastuti; Sunan Fanani; Imron Mawardi (Universitas Airlangga, 2017)
The aim of this study is to understand how coastal moslem’s creative economy development are. This study has used qualitative approach with study case strategy. Data collection has done by interviewing the informants i.e. Head of Kelurahan Sukolilo and Creative Industry’s stakeholder nearby Kenjeran, Surabaya. The result of this study is an appropriate model to develop coastal moslem’s socio-economics is a holistic-integrated developments. The model involved sort of stakeholders viz. fishermans, seafood crackers producers, the government, NGO’s, and universities. Keywords : Coastal Communities, Creative Economy, Kenjeran, Sosio-Economic Development